Efektivitas Komunikasi terhadap Pembentukan Kepribadian Anak Usia Dini: Studi Kasus di Desa Kramat, Bungah, Gresik - Ainiyah, Maslakhatul; Faqihatin (Jurnal Studi Multidisiplin Qomaruna, 2024)
Communication is a fundamental part of human life and is very important in the family, where parents act as the primary educators. Many parents work, resulting in reduced communication with their children. Communication within the family aims to strengthen social relationships and influence the development of the child's personality. Effective communication includes feelings of togetherness, mutual understanding, and emotional involvement. This research aims to describe the effectiveness of communication in shaping the personality of young children (early childhood) in the village of Kramat, Mengare Bungah, Gresik. Using a qualitative study design through observation and interview, we found that family communication is very important in influencing children's behavior. The more effective the communication between parents and children, the more the child's intrapersonal intelligence develops. Open communication between children and parents builds a positive self-concept in children, making them feel accepted and confident in making their own choices